The Argument of al-Fitrah to Prove The Existence of God Accordingto al-Maturidi - (:unkn) unknown (KARABUK UNIV, 2015)
Al-Maturidi is one of the foremost and most important thinkers in the history of Islamic thought. So that Al-Maturidi (333/944) is the most powerful figure in Abu Khanife School and has the biggest share in the establishment of Followers of Sunnah kalam. The aim of this study is to interpret the concept of al-fitrah, fitratallah (nature) and to investigate the possibility of rational knowing the existence of God with an intrinsic element of human (al-fitrah) according to the thinking of Al-Maturidi. The whole characteristics of all creatures, especially human being, brought by the genesis called nature(al-fitrah). The concept of al-fitrah contains all of beings in the world; accordingly, al-fitrah symbolizes creation of human. Humans are endowed with many biological, mental and spiritual abilities by born, not a result of work. Man also has innate moral-religious abilities that one of them is nature/fitrah. As a common agreement among psychologists and psychologists of religion, human is a believer as well as a thinker. This feature of believing comes from his nature. In the same way, Al-Maturidi believed that human have some dispositions from the birth. According to Al-Maturidi, creation is the consciousness of existence and uniqueness of God that is temperamental in all human beings. This feature of believing is inherent but the framework of this ability has not been determined yet. According to Al-Maturidi, God provides human a several inner qualities such as reason/aql, senses and feelings. These inner supports are actually facilities for human. With reference to the idea that the human is a cognizant (rational) creature, Al-Maturidi argues that he has reasonable and fair reasons for believing in a Creator; and he also uses the evidences such as disposition (skills coming with creation) that he links with the term nature (Khilkah). Talkingabout the fitrah of human is talking to the meaning and purpose the existence of human. Meaningfulness and purposefulness is the first law of the creation. Nature and dispositions, skills of human would indicate that there is a meaning and purpose, and hence points to the existence of God. In short, this article explores arguments of Maturidi regarding his opinions on knowing the existence of God by the fitrat/nature.
Keywords: Maturidi; Allah; Fitrah; Fitratullah; Human Being; Sunnah kalam